Inferior Glenohumeral Dislocation in a Division One Collegiate Wrestler - Alexander J. Gilmore; Alexander Walker (Journal of Sports Medicine and Allied Health Sciences: Official Journal of the Ohio Athletic Trainers' Association, 2016)
Background: A twenty-two year old male collegiate wrestler with no previous history of any shoulder injuries experienced an inferior glenohumeral dislocation on his right arm during practice. The athlete was in in a front headlock by a teammate who attempted to roll him. The athlete was forced into hyperflexion and abduction. The athlete felt a pop and his arm was “stuck” in approximately ninety degrees of abduction. An obvious deformity was palpable in his armpit. The athlete then proceeded to make his way to the athletic training room where he was able to relax and the dislocation reduced itself. After relocation the athlete had no obvious deformity, immediate swelling, or ecchymosis. He was experiencing very generalized soreness and was tender to palpate. His range of motion was very limited due to pain and we were unable to get a good evaluation on him at the time of injury. The next day he was still pretty sore and experienced pain with internal and external rotation. He was experiencing weakness in his rotator cuff and had diffuse neuropraxia. Differential Diagnosis: Labral Tear, shoulder instability, fracture to the humeral head. Treatment: The athlete saw the team physician the day of injury, was placed in a sling, and followed up with x-rays and a visit with the team physician the next day. No bony abnormalities were shown on the x-rays. The team physician discussed options of surgery or waiting with the athlete, who was pretty set on surgery, which he ended up getting the next week. He saw the team physician one week post-operation where the surgery and pictures were reviewed and explained. Athlete was doing well with no complaints. He had good range of motion for one week post-op. At this point we had to explain to him that he needed to be patient in order to let himself heal. We were told to continue his rehabilitation program of active internal and external rotation, passive supination/pronation, and putty squeezes and that he was allowed to do lower body activity if arm is not stressed. He is to see the team physician again in one week to assess his progress. Uniqueness: This case is fairly unique in comparison to other glenohumeral dislocations, due to the fact that the patient dislocated inferiorly, which is the least common direction of glenohumeral dislocation. Also, it is fairly unique that his dislocation was caused by his teammate because most people don’t have the strength to cause this injury especially with no prior history of shoulder injuries. Conclusion: In conclusion, it is important to discuss and take into account what your patient wants in terms of what steps to take in treatment of a glenohumeral dislocation, whether it be surgery first, or trying to rehabilitate the injury first and going from there.